Comparison of Efficacy of Dentifrice Containing 8% Arginine and 8% Strontium Acetate in Reducing Dentinal Hypersensitivity - Rizwan Zafar Langrial, Jawad Ahmad Kundi, Syed Midhat Batool, Syeda Lalarukh Saba Shah, Abid Rahim, Afaq Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the effect of dentifrice containing 8% strontium acetate and 8% arginine in reducing dentinal hypersensitivity. Study Design: Randomized clinical trial Place and Duration of Study: Department of Periodontology, Gandhara University Peshawar from 1st June 2014 to 31st October 2021. Methodology: Six hundred and twenty five patients were enrolled. The study was conducted in Sardar Begum Dental Hospital, Gandhara University Peshawar. They were divided into two groups; Group A were using dentifrice that contains 1450ppm sodium monofluorophosphate and 8.0% arginine whereas patients of group B were given dentifrice which contains 1040 ppm fluoride as sodium fluoride and 8% strontium acetate. Results: The mean difference was 0.59 of the initial less than one min Schiff values in both the groups. On the other hand, Schiff values in both the groups after 8 week application was 0.26. Likewise, difference in baseline mean values was 2.32 while 1 min post-application mean difference for strontium acetate and arginine was 7.13 and 2.88 respectively. Conclusion: Significant decreased in hypersensitivity in patient using the arginine and strontium acetate. Therefore it was an effective dentifrices in decreasing in office hypersensitivity.